Moral Sufism Islamic Boarding School Education (Examine the Value of Sufism from the Perspective of Imam Al-Ghazali in Ma'had TMI Al-Amien Prenduan) - ATIYATUS SYARIFAH; ACHMAD AS’AD ABD AZIZ; ABU AMAN (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2022)
As a result of modernization and industrialization, humans experience moral degradation which can reduce their dignity. Modern life as it is now often displays traits that are not commendable, especially in the face of this sparkling material. The traits that are not commendable are hirsh, namely excessive desire for material things. This article aims to examine more deeply the values ​​of moral sufism in Islamic boarding schools, especially Ma'had TMI al-Amien Prenduan Sumenep Madura by using the study of Muhammad Al-Ghazali's thoughts. This study used a qualitative research method with the type of library research or literature study which is descriptive analysis in nature. Basically, this literature study uses scientific journals or articles, books, and references that are relevant to research. Al-Ghazali's Sufism values ​​include: Tazkiyatun Nafs (cleansing the soul),Mujahadah (not following lust),Ridloh (Exercise),Get over it (alone),Asceticism (away from the world). The process of instilling the values ​​of Al-Ghazali's Sufism in Islamic boarding schools. Process of moral knowledge (Moral Knowledge) through book study:Kitab Ihya' Ulumuddin, Minhajul Abidin, Bidayatul Hidayah, Qifayatul Atqiya'.